Preparation method of vulcanized MIL-88B (Fe) composite material and application of vulcanized MIL-88B (Fe) composite material in photocatalytic nitrogen reduction

By growing FexSy in situ on MIL-88B(Fe), a stronger binding force MIL-88B(Fe)@FexSy composite was prepared, which solved the problem of easy recombination of photogenerated electrons and holes and poor nitrogen adsorption capacity, and achieved efficient photocatalytic nitrogen reduction performance.

CN120243127APending Publication Date: 2025-07-04CHINA THREE GORGES UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510243418.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

In the field of photocatalytic nitrogen reduction, existing semiconductor photomaterials are prone to recombination with photogenerated electrons and holes and have poor nitrogen adsorption capabilities, which limits their development.

Method used

MIL-88B(Fe) is used as the vulcanization framework to provide more reaction sites by growing FexSy in situ, and the composite material MIL-88B(Fe)@FexSy is prepared by electrodeposition method to enhance the binding force and light absorption capacity of the material.

Benefits of technology

The photocatalytic nitrogen reduction performance is significantly improved, and the NH4+ yield reaches more than 7 times that of pure MIL-88B (Fe). The composite catalyst is strong in stability and can be recycled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120243127A_ABST
    Figure CN120243127A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an MIL-88B (Fe) composite material and application of the MIL-88B (Fe) composite material in photocatalytic nitrogen reduction. The field focuses on preparation of metal organic framework derived materials and photocatalytic conversion technologies. MIL-88B (Fe) is adopted as a core catalyst, the composite material MIL-88B (Fe)-coated FexSy is successfully prepared through in-situ vulcanization by a rapid and simple electro-deposition vulcanization method, the MIL-88B (Fe)-coated FexSy serves as a vulcanization framework, more reaction sites are provided for in-situ growth of the FexSy, and variable valence metal Fe serves as a reaction center for reducing nitrogen into ammonia products. Meanwhile, the FexSy grows uniformly on the metal frame by using an electro-deposition method, and the bonding force between the compounds is stronger and more stable. Under a solid-liquid reaction condition, after 2 hours of light treatment, the SMFe-5 composite material shows excellent photocatalytic performance, nitrogen is successfully reduced to NH4 < + >, and the yield of NH4 < + > is up to 73.08 [mu] mol.g <-1 >, which is about more than 7 times of that of a single MIL-88B (Fe) catalyst and more than 4 times of that of a single FexSy catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical field involved in the present invention is the preparation of MOF-derived materials and the field of photocatalytic nitrogen reduction technology. Specifically, it is a preparation method of MIL-88B(Fe) composite materials and its photocatalytic application. Background Art

[0002] With the substantial growth of the world's population, the issue of food supply has attracted people's attention. Relying solely on natural nitrogen fixation to provide nitrogen fertilizers far from meets the actual needs of modern society. To overcome the kinetic barriers of nitrogen fixation reactions, the development of artificial nitrogen fixation is highly necessary. Regarding the means of artificial nitrogen fixation, researchers have conducted a large number of theoretical studies and practical operations, and developed various nitrogen fixation processes. Under the dual requirements of resource shortage and green production, photocatalytic technology has become a major research focus. This technology uses solar energy as the energy source and water as the raw material to prepare NH3 through a simple process flow. This method effectively avoids the harsh production conditions in traditional industrial nitrogen fixation and has no pollutant emissions, alleviating the severe environmental problems in today's society. The development of this process has great practical significance and guiding value in the field of nitrogen fixation and is an ideal nitrogen fixation technology.

[0003] Currently, many photocatalysts of semiconductor optical materials have been applied by predecessors in the field of photocatalytic nitrogen reduction. However, due to limitations such as the easy recombination of photo-generated electrons and holes and poor nitrogen adsorption ability, the development of semiconductor materials in the photocatalytic field has been restricted.

[0004] Metal-organic frameworks (MOFs) have characteristics such as high crystallinity, ultra-high specific surface area, variable pore size, and high-density coordinatively unsaturated metal sites, which have attracted extensive attention in the field of nitrogen photoreduction. By modifying organic ligands, metal ions, and active components, the composition and properties of MOFs can be regulated, which can expand the light absorption range of MOFs, promote electron transfer, and enhance the nitrogen photoreduction performance of MOFs.

[0005] Taking MIL-88B(Fe) as the sulfurization framework to provide more reaction sites for the in-situ growth of Fe x S y The variable-valence metal Fe is the reaction center for the reduction of nitrogen to ammonia products. At the same time, in-situ sulfurization makes the binding force between the composites stronger and more stable. As a magnetic material, this material also helps with recycling and reuse. Summary of the Invention

[0006] Aiming at the above technical problems, the purpose of the present invention is to provide a preparation method of MIL-88B(Fe) composite materials. In this composite material, MIL-88B(Fe) is used as the sulfurization framework to provide more reaction sites for the in-situ growth of Fe x S yProvide more reaction sites, thus greatly enhancing the nitrogen photocatalytic conversion performance of MOFs.

[0007] For the above purpose, the preparation method adopted in the present invention is as follows: Suspend MIL-88B(Fe) in an organic solvent, then coat it on the FTO electrode, and after drying, use it as the working electrode. Use the sulfiding agent solution as the electrolyte, and after depositing for a period of time under a constant voltage, wash and dry to obtain the sulfided MIL-88B(Fe) composite material.

[0008] The described MIL-88B(Fe) is obtained by adding an iron salt and a ligand to a solvent, adding a precursor solution, and then performing a thermal reaction at 80 - 120 °C to obtain MIL-88B(Fe).

[0009] The described iron salt includes any one of FeCl3·6H2O, Fe(NO3)3·9H2O, and Fe2(SO4)3·H2O.

[0010] The described reaction solvent is one or more of N,N-dimethylformamide, N,N-diethylformamide, and tetrahydrofuran; the ligand is terephthalic acid; among them, the molar ratio of the iron salt to terephthalic acid is 1:2 - 1:1; the precursor solution is sodium hydroxide, polyvinylpyrrolidone, or acetic acid.

[0011] The described organic solvent is selected from one or more of methanol, ethanol, acetonitrile, or DMF.

[0012] The described sulfiding agent is selected from one or a mixture of several of disulfur dichloride S2Cl2, phosphorus pentasulfide P2S5, sodium sulfide Na2S, and thiourea.

[0013] The addition amounts of MIL-88B(Fe) and the sulfiding agent are the molar ratio of Fe to S, 1:7 - 1:13.

[0014] The electrodeposition voltage is -0.5~-2.0 V (vs. Ag / AgCl); the heating temperature is 30~60 °C; the deposition time is 10 - 15 min.

[0015] For the technical solution of the present invention, the present invention relates to the application of the sulfided MIL-88B(Fe) composite material prepared by the described method in the photocatalytic nitrogen fixation reaction.

[0016] The described sulfided MIL-88B(Fe) composite material catalyzes the conversion of nitrogen to NH4 under photocatalysis + in the application.

[0017] The application process includes the following steps: Put MIL-88B(Fe)@Fe x Sy The composite powder catalyst was poured into a quartz bottle containing 100 mL of deionized water, and then the quartz bottle containing the catalyst solution was placed in an ultrasonic oscillator and ultrasonically treated for 30 min to form a homogeneous solution. Subsequently, the above quartz bottle was placed under dark conditions and continuously bubbled with nitrogen for 30 min. The nitrogen fixation performance test was carried out under the xenon lamp illumination condition of 300 W for 2 h, and the light source was 10 cm away from the top of the quartz bottle. After the photocatalytic test was completed, the catalyst in the reaction solution was removed by centrifugation at a speed of 10000 r min -1 at a speed of.

[0018] An ion chromatograph was used to test the concentration of NH3 / NH4 + generated during the reaction.

[0019] The wavelength range of the light source used must be within the light absorption range of the material, λ > 420 nm.

[0020] In the invention, "room temperature" refers to the conventional ambient temperature, which can be 15 - 30 °C.

[0021] The advantages of the present invention are as follows: (1) In the present invention, through the in-situ sulfidation method, using MIL-88B(Fe) as the substrate, a sulfurizing agent is used to grow Fe x S y on the surface of the metal-organic framework. The polyhedral structure of MIL88 provides a large number of growth sites for Fe x S y , and the in-situ growth method makes the combination between the two compounds closer, thereby enhancing the stability of the composite catalyst.

[0022] (2) The present invention uses the electrochemical deposition method to fabricate the catalyst. Compared with methods such as solvothermal method and calcination method, the fabrication time is shortened, and Fe x S y grows uniformly.

[0023] (3) Under the synergistic effect of MIL-88B(Fe) and Fe x S y in the present invention, the light absorption ability of the composite catalyst is enhanced, and the light utilization range is expanded. The interfacial structure between MIL-88B(Fe) and Fe x S y increases the lifetime of photo-generated carriers, reduces the annihilation of electron-hole pairs, accelerates electron transfer, and improves the electron utilization rate.

[0024] (4) The present invention tested the effects of vulcanizing agents, vulcanization ratios, and vulcanization times on the composite material in the photocatalytic nitrogen fixation reaction, determined the optimal vulcanizing agent, addition amount, and vulcanization time, and its performance is 7 times that of pure MIL-88B(Fe). At the same time, the composite catalyst has strong stability, can be recycled, and has stable nitrogen fixation performance. Description of the Drawings

[0025] Figure 1 It is the XRD pattern of MIL-88B(Fe) in Example 5 of the present invention.

[0026] Figure 2 It is the nitrogen fixation performance diagram of Examples 1-6 of the present invention.

[0027] Figure 3 It is the nitrogen fixation performance diagram of Examples 5, 7-9, MIL-88B(Fe), and Fe x S y of the present invention.

[0028] Figure 4 It is the four-cycle nitrogen fixation performance diagram of Example 7 of the present invention.

[0029] Figure 5 It is the XRD comparison diagram of Examples 1 and 7 of the present invention before and after nitrogen fixation. Detailed Embodiments

[0030] The present invention will be further described below in conjunction with the embodiments and the drawings.

[0031] Example 1 (1) Preparation of MIL-88B(Fe): Weigh 1 mmol of FeCl3·6H2O and 1 mmol of H2BDC and place them in a 100 mL reaction kettle, dissolve them in 50 mL of DMF, add 4 mL of sodium hydroxide solution with a concentration of 2 moL / L, stir for 30 min to form a uniform yellow solution, ultrasonicate at room temperature for 30 min, heat at 100 °C for 10 h to obtain MIL-88B(Fe), naturally cool to room temperature, centrifuge to collect the product, wash it several times with methanol, DMF, and deionized water, and vacuum dry at 60 °C for 10 h.

[0032] Use XRD to characterize and test MIL-88B(Fe) (2) Preparation of MIL-88B(Fe)@Fe x S y composite material: Suspend 50 mg of MIL-88B(Fe) in 5 mL of ethanol solution, uniformly coat it on a 2 cm 2On a clean FTO electrode, it was dried. Then, 0.1587 g of potassium sulfide as a sulfurizing agent was added with an Fe:S molar ratio of 1:7 and dissolved in 50 mL of deionized water, and the solution was ultrasonicated for 30 minutes for uniform diffusion. In a three-electrode system, with the sulfide solution as the electrolyte and the FTO electrode as the working electrode, deposition was carried out at -0.5 V for 15 min. The electrode was rinsed and dried in a vacuum drying oven at 60 °C for 10 h, and then the catalyst on the electrode surface was scraped off to obtain the composite catalyst MIL-88B(Fe)@Fe x S y . It was denoted as SMFe-1. Example 2 (1) The preparation of MIL-88B(Fe) was the same as in Example 1.

[0033] (2) The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as in Example 1, except that the sulfurizing agent was replaced with 0.1082 g of thioacetamide. The obtained composite catalyst was denoted as SMFe-2.

[0034] Example 3 (1) The preparation of MIL-88B(Fe) was the same as in Example 1.

[0035] (2) The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as in Example 1, except that the sulfurizing agent was replaced with 0.1124 g of sodium sulfide. The obtained composite catalyst was denoted as SMFe-3.

[0036] Example 4 (1) The preparation of MIL-88B(Fe) was the same as in Example 1.

[0037] (2) The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as in Example 1, except that the sulfurizing agent was replaced with 0.1096 g of thiourea. The obtained composite catalyst was denoted as SMFe-4.

[0038] Example 5 (1) The preparation of MIL-88B(Fe) was the same as in Example 1.

[0039] (2) The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as in Example 1, except that the sulfurizing agent was replaced with 0.1944 g of disulfur dichloride. The obtained composite catalyst was denoted as SMFe-5.

[0040] Example 6 (1)The preparation of MIL-88B(Fe) was the same as that in Example 1.

[0041] (2)The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as that in Example 1, except that the sulfurizing agent was changed to 0.0640 g of phosphorus pentasulfide. The obtained composite catalyst was denoted as SMFe-6.

[0042] Example 7 (1)The preparation of MIL-88B(Fe) was the same as that in Example 5.

[0043] (2)The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as that in Example 5, except that the applied voltage was changed to -1.0 V. The obtained composite catalyst was denoted as SMFe-7.

[0044] XRD was used to characterize and test SMFe-7.

[0045] Example 8 (1)The preparation of MIL-88B(Fe) was the same as that in Example 5.

[0046] (2)The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as that in Example 5, except that the applied voltage was changed to -1.5 V. The obtained composite catalyst was denoted as SMFe-8.

[0047] Example 9 (1)The preparation of MIL-88B(Fe) was the same as that in Example 5.

[0048] (2)The preparation process of the MIL-88B(Fe)@Fe x S y composite material was the same as that in Example 5, except that the applied voltage was changed to -2.0 V. The obtained composite catalyst was denoted as SMFe-9.

[0049] As a comparison, pure Fe x S y was prepared separately. The scheme referred to relevant papers. Specifically, 0.48 g of FeCl3·6H2O and 1.89 g of disulfur dichloride were dissolved in 50 mL of deionized water, and the solution was ultrasonically treated for 30 minutes for uniform diffusion. In a three-electrode system, the FTO electrode was used as the working electrode, and deposition was carried out at -1.0 V for 15 min. The electrode was rinsed and dried in a vacuum drying oven at 60 °C for 10 h, and then the catalyst Fe x Sy . For the MIL-88B(Fe)@Fe of Examples 1-9 x S y samples and MIL-88B(Fe), Fe x S y Perform photocatalytic nitrogen fixation performance tests.

[0050] The specific photocatalytic nitrogen fixation experiment is as follows: Take 10 mg of the composite catalyst and dissolve it in a quartz bottle containing 100 mL of deionized water. Then place the quartz bottle in an ultrasonic oscillator and ultrasonicate for 30 min to form a homogeneous solution. Subsequently, place the above quartz bottle under dark conditions and continuously bubble nitrogen at a rate of 50 mL / min for 30 min. Conduct a 2-h nitrogen fixation performance test under the illumination of a 300-W xenon lamp, with the light source 10 cm away from the top of the quartz bottle. After completing the photocatalytic test, centrifuge at a speed of 10000 r min -1 to separate the reaction solution from the catalyst, and take the clarified water sample for ammonia nitrogen product testing by ion chromatography.

[0051] The nitrogen fixation performance of Examples 1-6 is as Figure 2 shown. It can be seen that the nitrogen fixation performance of the sample SMFe-5 using sulfur dichloride as the sulfiding agent is the highest, reaching 48.72 μmol g -1 , which is 35% higher than the ammonia production rates of potassium sulfide and sodium sulfide. This is because potassium sulfide and sodium sulfide dissolve in water to be alkaline, which has a destructive effect on the metal-organic framework.

[0052] For Examples 5, 7-9, MIL-88B(Fe) and Fe x S y The nitrogen fixation performance is as Figure 3 shown. When the deposition voltage of Example 7 is -1.0 V, the nitrogen fixation performance of the catalyst is the highest, reaching 73.08 μmol g -1 . It is 7 times and 4 times that of pure MIL-88B(Fe) and Fe x S y . When the deposition voltage is increased, the nitrogen fixation performance of the catalyst decreases. This is because when the voltage is too high, MIL-88B(Fe) is over-sulfided, resulting in too high a content of Fe x S y in the composite catalyst.

[0053] The present invention also conducted cyclic nitrogen fixation tests on the composite catalyst SMFe-7 of Example 7 to explore whether it has stable catalytic activity. As Figure 4 shown, it still has stable nitrogen fixation reduction performance after four cycles.

[0054] To investigate the surface structure stability of the composite catalyst, Example 1 and Example 7 were selected, and their XRD patterns before and after the photocatalytic nitrogen fixation reaction were compared. The results are as Figure 5 shown. The XRD diffraction peaks of SMFe-7 remained basically unchanged before and after the reaction. However, in the XRD pattern after the SMFe-1 reaction, the characteristic peaks representing MIL-88B(Fe) between 7° and 10° were not observed, and the peak width of the characteristic peaks of iron sulfide increased, the relative intensity decreased, and the crystal form was destroyed. This verified that the sulfidation degree of the composite material SMFe-7 had good structural stability.

[0055] The above content is a preferred example of the present invention, but the present invention should not be limited to the content disclosed in this example. Therefore, all equivalent or modified completions made without departing from the spirit disclosed by the present invention fall within the protection scope of the present invention.

Claims

1. A preparation method of a sulfurized MIL-88B(Fe) composite material, characterized in that, It includes the following steps: Suspend MIL-88B(Fe) in an organic solvent, then coat it on the FTO electrode. After drying, it serves as the working electrode, and the sulfiding agent solution serves as the electrolyte. After sedimentation for a period of time under heating and a constant voltage, wash and dry to obtain the sulfided MIL-88B(Fe) composite material.

2. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 1, characterized in that, The MIL-88B(Fe) described above is obtained by adding an iron salt and a ligand to a solvent, adding a precursor solution, and then performing a thermal reaction at 80-120 °C to obtain MIL-88B(Fe).

3. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 2, characterized in that, The iron salt includes any one of FeCl3·6H2O, Fe(NO3)3·9H2O, and Fe2(SO4)3·H2O.

4. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 1, wherein, The reaction solvent is one or more of N,N-dimethylformamide, N,N-diethylformamide, and tetrahydrofuran; the ligand is terephthalic acid; among them, the molar ratio of the iron salt to terephthalic acid is 1:2 to 1:1; the precursor solution is sodium hydroxide, polyvinylpyrrolidone, or acetic acid.

5. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 1, characterized in that, The organic solvent is selected from any one of C1-C5 alcohols.

6. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 1, characterized in that, The sulfiding agent is selected from one or a mixture of several of disulfur dichloride S2Cl2, phosphorus pentasulfide P2S5, sodium sulfide Na2S, and thiourea.

7. The preparation method of the sulfurized MIL-88B(Fe) composite material according to claim 1, wherein, The addition amounts of MIL-88B(Fe) and the sulfiding agent are the molar ratio of Fe to S, 1:7 to 1:

13.

8. The preparation method of the vulcanized MIL-88B(Fe) composite material according to claim 1, characterized in that, The electrodeposition voltage is -0.5~-2.0 V (vs. Ag / AgCl); the heating temperature is 30~60 °C, and the deposition time is 10-15 min.

9. Application of the sulfided MIL-88B(Fe) composite material prepared by the method according to any one of claims 1-8 in the photocatalytic nitrogen fixation reaction.

10. The application according to claim 9, wherein Application of Sulfurized MIL-88B(Fe) Composite Material in Photocatalytic Conversion of Nitrogen into NH4 + ​